Identification and characterization of linear epitopes of monoclonal antibodies against the capsid proteins of small ruminant lentiviruses - Ma, Xiaohua; Gao, Min; Zhang, Xiangmin; Ma, Weiwei; Xue, Fei; Wang, Xue-Feng; Wang, Xiaojun (Frontiers in Microbiology, 2024)
Maedi-visna virus (MVV) and caprine arthritis encephalitis virus (CAEV) are members of a group of genetically highly homologous lentiviruses collectively referred to as small ruminant lentiviruses (SRLVs). SRLVs can infect sheep, goats and other small ruminants, causing multisystemic disease with progressive and persistent inflammatory changes, severely reducing animal productivity and impeding animal trade. The capsid protein of SRLVs, p28, is highly conserved among strains and is a commonly used marker for the detection of SRLVs. In this study, two monoclonal antibodies (mAbs), designated G8F7 and A10C12, against p28 were generated using a recombinant p28 protein expressed in Escherichia coli as an immunogen. Functional analysis showed that these two monoclonal antibodies could be used in iELISA, immunofluorescence assays (IFA) and western blot assays to detect p28 or Gag precursor proteins of SRLVs. Two linear epitopes, 61GNRAQKELIQGKLNEEA77 (E61-77) and 187CQKQMDRVLGTRVQQATVEEKMQACR212 (E187-212), which are recognized by G8F7 and A10C12, respectively, were identified through truncation of the GST-fused p28. Amino acid sequence alignment showed that the epitope E61-77 is conserved among SRLVs, with a dominant mutation site (K72R) that does not disrupt recognition by G8F7. E187-212 was found to exhibit variability among SRLVs, but the majority of mutant epitopes are recognized by A10C12, with the exception of a mutant epitope from an isolate with undefined subtypes from Ovis aries, which was not recognized. These findings may facilitate future study of SRLVs and promote the development of methods for the detection of these viruses.